PENGARUH PENGGUNAAN MEDIA POWER POINT TERHADAP AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA ISLAM BAWARI PONTIANAK - Munaroh, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research about "the Effect of using of Power Point Media on student learning activity on economy class X Â of Islamic High School Bawari Pontianak". The purpose of this research is to know how much influence the use of media Power Point toward the activities of student learning in the subject the economy class X SMA Islam Bawari Pontianak. The method used in this research is the method of the experiment with the form of quasi experimental research design. The total samples in this research as much as 70 students . teknik data collection with direct communication technique (interview guidance), communication technique is not directly (observation sheet of learning activities students), and the technique of documentary studies in this research instrument tests using the validity test and normalitas test. For data processing techniques using independent test sample t test. Based on the results of the test calculations of the test statistics t Mann Whitney obtained the value of the significance (Sig 2-tailed) is 0,000 , the value of the significance < 0.05 (0,000 < 0.05) then the Ho was rejected and Ha accepted. The conclusion of this research is that the use of learning media based on the Power Point can affect the students learning activities on economic subjects.Keywords: Learning Activity, Power Point Media. Â